Affirmative Action to Increase the Women Representation in Legislative: a Study in Sijunjung Regency, West Sumatera Province - Astika Ummy Athahirah (Jurnal Multidisiplin Madani, 2022)
This study aims to find an overview of the inhibiting factors that cause a low representation of women and the strategies needed to increase women's representation in the Sijunjung Regency. This semi-qualitative research design uses the Manual Data Analysis Procedure (MDAP). The conclusions are that the inhibiting factors come from internal and external factors. Meanwhile, the strategies to solve the inhibiting factors optimize affirmative action through several activities. Therefore, this research dramatically contributes to efforts to increase the representation of women in politics to realize various public policies that are friendly to women.